Pengaruh Akuntabilitas, Pengetahuan Audit Dan Gender Terhadap Kualitas Hasil Kerja Auditor Internal (Studi Empiris Pada Kantor Inspektorat Aceh) - Aprilia Ulantika Sari; Surbakti Karo-Karo (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
The problem in this study shows that there are still auditors who make mistakes during auditing. The implementation of the quality of audit results carried out by auditors is still a public concern, because it is caused by existing findings and is not detected by the Inspectorate apparatus as internal auditors. This phenomenon indicates that the case of audit quality is still happening. This shows that the results of the audits conducted by the local government internal control apparatus have not produced good audit quality. For this reason, improvements are still needed from time to time to get good audit quality standards. This study aims to obtain empirical evidence that can be tested for hypotheses and to determine the effect of the variables of accountability, audit knowledge, and gender on the variables of the quality of the work of internal auditors. The population in this study were 52 auditors / internal auditors of the Aceh Inspectorate. The sample in this study were several auditors in the Aceh Inspectorate with certain criteria.The sampling technique in this study was purposive sampling, namely the selection of samples based on certain considerations by meeting the criteria set by the researcher. In this study, the data were tested and analyzed through validity test, reliability test, classical assumption test, normality test, multicollinearity test, coefficient of determination (R2) test, t statistic test and F statistic test. The results of this study indicate that the influence of accountability on the quality of the work of internal auditors shows insignificant results, with a significance level of 0.270. The effect of audit knowledge on the quality of the work of the internal auditors showed significant results, with a significance level of 0.021, and the effect of gender on the quality of the work of internal auditors showed insignificant results, with a significance level of 0.992. The conclusion of this study shows that accountability, audit knowledge, and gender simultaneously and significantly have no effect on the quality of the work of internal auditors.